2018
DOI: 10.1186/s12888-018-1845-1
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine as add-on to antidepressant medication in therapy refractory major depressive disorder patients with increased inflammatory activity: study protocol of a double-blind randomized placebo-controlled trial

Abstract: BackgroundA subgroup of depressed patients with increased inflammatory activity was shown to be more susceptible to develop Treatment Resistant Depression (TRD). Earlier studies with anti-inflammatory drugs have shown benefits in the treatment of major depressive disorder (MDD), but the effects are expected to be higher in patients with increased inflammatory activity. Supplementation of N-acetylcysteine (NAC) to ongoing antidepressant therapy may positively influence outcome of depression treatment in these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…We used NAC as a positive control because the antidepressant-like effects of NAC have been explored in several studies (Ferreira et al, 2008; Costa-Campos et al, 2013). One study group is planning to evaluate the inflammation-inhibiting NAC effects on depressive disorder in a randomized placebo-controlled trial (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We used NAC as a positive control because the antidepressant-like effects of NAC have been explored in several studies (Ferreira et al, 2008; Costa-Campos et al, 2013). One study group is planning to evaluate the inflammation-inhibiting NAC effects on depressive disorder in a randomized placebo-controlled trial (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In MDD, inflammatory and oxidative processes seem to be part of the pathophysiology of depression. Inflammation markers, proinflammatory cytokines, acute phase proteins, and adhesion molecules are usually elevated in patients with this disorder, contributing to neuroinflammation that appears to be associated with structural and functional abnormalities in the brain and a lower therapeutic response [ 144 ]. Although NAC is a strong candidate for adjunctive treatment of depression, oral supplementation of 1000 mg/day (2 capsules of 500 mg twice daily) associated with the usual treatment of the disease, when compared to placebo, did not produce positive effects on treatment of individuals with MDD (moderate to severe) at the end of 12 weeks.…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…Third, higher levels of IL-6 or CRP can predict subsequent development of depressive symptoms (e.g., tiredness, lack of energy, sleep problems, and changes in appetite) [23, 24]. Fourth, increased inflammatory activity leads to greater susceptibility to treatment-resistant depression (TRD) [25]. Fifth, intestinal microbes can influence tryptophan metabolism and cause changes in levels of gamma-aminobutyric acid, dopamine, and serotonin [26, 27].…”
Section: Link Between Inflammation and Rmddmentioning
confidence: 99%
“…Yet, neuroimaging findings and peripheral biomarker measurements in patients with rMDD are relatively scarce. A recent study protocol of a double-blind randomized placebo-controlled trial suggested that increased inflammatory activity indicated a greater susceptibility to TRD [25]. Future studies should thus investigate whether there is any cross-sectional or longitudinal association of peripheral biomarker measurements with neuroimaging in depression relapse.…”
Section: Neuroimaging Biomarkers Related To Rmddmentioning
confidence: 99%